Preoblikovanje regionalnih zavodov za zdravstveno varstvo - Grmek-Košnik, Irena (Zdravstveno varstvo, 2007)
The government perceives a need for more efficient utilization of resources, as well as for achieving better results through changes in the organisation ofpublic health service, which, in many ways, is not in line with the European Union legislation. Regional institutes of public health (ZZV) are public institutions which gain a large share of income (75%) through their services in the market, and are therefore run as companies. Publicly funded public health services are provided in cooperation with the national Instituteof Public Health (IVZ) within the framework of the national programme. The national institute and nine regional institutes employ approximately 1,000 people altogether. The proposed changes to the present legislation, which encompass the law on health care services, include transforming regional institutes into agencies. Individual agencies would employ seven to fifteen people (public health teams). ZZVs would be split into two parts; the aforementioned public health team, financed through the national budget, and an independent company or a public limited company. Ownership would be transfered from the state to regions or municipalities. Thenew ZZVs would be organised as public limited companies, pure economic societies, or, will be defined by the new or revised legislation.
Keywords: javno zdravje; reorganizacija; Slovenia; Slovenija; zavodi za zdravstveno varstvo; zdravstveni zavodi